The Mirror of Realism. Knowledge and Affectivity of the Literary Text - Menzio, Pino (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2016)
An analysis of the metaphor of the mirror confirms that literary realism is not a mere and optically objective reflection of reality, as meant by the more naïve versions of philosophical realism. On the contrary, it’s an hermeneutical interpretation of the world, driven by affectivity and emotions.